Evaluation of adsorption and coagulation characteristics of humic acids preceded by alternative advanced oxidation techniques - KERÇ, ASLIHAN (ELSEVIER, 2007)
Humic substances mainly humic acids constitute the major fraction of natural organic matter in water supplies. Humics express diverse actions primarily related to the formation of potentially harmful disinfection by products (DBPs). Therefore, the removal of DBP precursors through numerous treatment techniques gains high importance. Besides the conventional treatment processes, the applications of advanced oxidation techniques are considered as effective tools for the elimination of humic acids (HAs) from natural waters. In the present study, both the adsorption and coagulation characteristics of humic acid samples are evaluated subsequent to pretreatment by photocatalytic oxidation and ozonation. The changes in preoxidized humic acid solutions are assessed in relation to the alterations induced in the UV-vis and fluorescence spectroscopic properties. The removal efficiency of color in terms of Color(436) and aromaticity with respect to UV254 are presented relevant to each treatment step. Major key parameters such as the selection of coagulant types (alum and ferric chloride), coagulant aids (ionic and non-ionic polyelectrolyte) and optimum coagulant dose were comparatively discussed. The adsorption characteristics of powdered activated carbon (PAC) and granular activated carbon (GAC) were investigated.
Keywords: humic acid; ozonation; photocatalysis; adsorption; coagulation; NATURAL ORGANIC-MATTER; ACTIVATED-CARBON; AQUATIC HUMUS; FULVIC-ACIDS; FLUORESCENCE; OZONATION; REMOVAL; WATER